Gender effects of agricultural cropping work and nutrition status in Tanzania - Komatsu, Hitomi; Malapit, Hazel J.; Balagamwala, Mysbah (Public Library of Science, 2019)
Although agriculture is an important source of food and income for food expenditures, women’s involvement in the agricultural cropping production process could increase their work load and reduce their BMI. Using three waves of the Tanzania National Panel Survey, we investigate the extent to which time spent in agricultural crop production affects women and men’s nutritional status among non-overweight individuals (age 20–65). We also test whether the impact of agricultural cropping work on nutritional status is modified by access to agricultural equipment, and whether gender differences exist. The study finds that time spent in agricultural cropping work is negatively associated with BMI for non-overweight individuals, albeit of small magnitude, and this finding is consistent across different crop production processes. This suggests that agricultural interventions should not ignore the implications of increasing work intensities on nutrition. While increased agricultural production could improve nutritional status by increasing agricultural income and food, the gains in nutritional status could be offset by an increase in work effort of doing agricultural work. Our results suggest that it is possible that access to equipment reduced effort for one production activity, but increased work for other activities in the production process, such as in harvesting. Furthermore, we find that the BMI of women in households with a hand powered sprayer is positively related to time spent in weeding, fertilizing, and non-harvest activities, while it is negatively correlated for men. It is possible that access to a hand powered sprayer may have helped reduce women’s work, for example, in weeding, while this was not the case for men’s work such as in ridging and fertilizing. Further disaggregation of agricultural activities in the dataset would have been helpful to provide more insights on the gender roles.